Inclusive communities, exclusionary city, planning n/a? Mapping condomínios fechados semi-quantitatively in Lisbon, Cascais (and Barreiro) - Tulumello, Simone (2018)
If one is seeking a prototypical exemplification of exclusionary urban development, the gated community is what they are looking for. Gated communities are residential developments, originating in the usa and flourishing all around the urban planet. They are characterised, first, by spatial seclusion with respect to the outer urban space – more often in the form of multi-villa fenced estates; and, second, variable degrees of social homogeneity. Gated communities are idealised and advertised as inclusion spaces among peers sharing the same class – and typically, if silently, the same self-perception of race/ethnicity – and exclusion spaces with regard to urban “outsides”, considered to be dangerous, chaotic or simply too mixed. In the usa, the success of gated communities after the Second World War was associated with the “white flight”, the abandonment, by white middle and upper classes, of “inner cities” where black (and poor) immigrants were settling in; and hence suburbanisation.